Religious Authority, Colonial Governance, and Resource Contestation: Reexamining the 1920 Iraq Revolution - Habib Badawi; Agus Mahfudin Setiawan (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study explores the multidimensional dynamics of the 1920 Iraqi Revolution by analyzing the intersection of Shi'i religious authority, British colonial administration, and Indigenous resistance. It focuses on how Mirza Muhammad Taqi Shirazi’s leadership mobilized anti-colonial resistance by navigating complex tribal politics and contestations over resources in the Hilla Division. Employing a multidisciplinary framework—drawing on postcolonial theory, religious authority, and resource mobilization theory—this research analyzes British administrative records and Iraqi local accounts. Comparative historical analysis is used to examine water management, taxation, and religious authority structures before and during the revolution. The findings reveal that Shirazi’s spiritual leadership legitimized and structured collective resistance, bridging divides between tribes and urban populations. The British-controlled Hindiya Barrage caused disruptions in irrigation and land use, triggering socioeconomic tensions that intensified opposition. Furthermore, contradictions within the colonial bureaucracy opened opportunities for effective local resistance. The revolution ultimately compelled a shift from direct to indirect British rule, shaping Iraq’s political trajectory. By moving beyond nationalist interpretations, this study highlights the role of religious authority, hydraulic politics, and colonial governmentality. It offers broader insights into anti-colonial movements where spiritual leadership and ecological control were central to resistance strategies against imperial dominance.